Shakespeare’S Play Titus Andronicus: a Therapeutic Practice of Violence and Cannibalism: Exploring the Significance of Violence and Cannibalism in Shakespeare's Titus Andronicus (Journal of Advances and Scholarly Researches in Allied Education, 2015)
In Shakespeare’s TitusAndronicus, the audience are confronted with a nightmarish series of violentacts, increasing in ferocity and volume, which culminate in the Roman generalTitus feeding Tamora, Queen of the Goths, her sons ‘baked in a pie | Whereoftheir mother has daintily fed’ (5.3.59-60).2 Much of the play’s reputation hasbeen built upon the graphic depictions and reports of violence, which commencein state sanctioned execution, worsen to rape and mutilation, and climax incannibalism. There is little doubt that the scale and manner of the violence inTitus Andronicus is horrific,but the significance and symbolic value of the acts has often been overlooked.